ProRobot: An Experience Report of an Introduction to Programming and Robotics Course - Araújo, Thabatta Moreira Alves De; Silva, Anderson Ribeiro De Oliveira Santos; Silva, Alisson Marques Da; Maia, Eduardo Habib Bechelane; Silva, Michel Pires Da (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2023)
This article describes the experience of an Intro-duction to Programming and Robotics course offered to the community since 2016 for elementary school students with no prior exposure to programming. The objective of the course is to foster logical and computational reasoning and creativity and attract potential talents to the field of computer science. The course was designed to be a blended methodology aimed at developing active methodologies such as flipped classrooms, maker culture, and gamification from a Freirean perspective. It seeks to promote critical thinking, student empowerment, and meaningful learning experiences. The achieved results of the course encompass student education, skill development, scientific dissemination, and integration between the school and the community.